Impact of climate change on agriculture in eastern Uttar Pradesh and Bihar states (India) - KUMAR, ARVIND; TRIPATHI, PADMAKAR; SINGH, K.K.; MISHRA, A.N. (MAUSAM, 2011)
Production of crops is greatly influenced by weather phenomena and therefore any change in climate will have major effects on crop yield and productivity. Using NYD analysis for prediction of crop yield on seasonal basis, it has been observed that maximum temperature may cause the reduction in yield of rice in Eastern Uttar Pradesh by 1.0 to 1.1% per ha by 2020. Similarly, minimum temperature may decrease the yield of rice by 1.5 to 1.9% per ha in Eastern Uttar Pradesh. From future scenario of rainfall it was observed that south-west monsoonal rainfall would be the major factor for controlling the yield of rice. The role of maximum temperature for wheat production in Bihar state is more significant as compared to Eastern Uttar Pradesh. The model predicts that wheat yield may decrease by 5-6% in Bihar state due to increase in maximum temperature by the end of 2080 whereas this decrement in Eastern Uttar Pradesh may be 1.5-2.0%.